POSTER UTILIZATION AS A PREVENTION OF DRUG ABUSE IN ADOLESCENTS THROUGH SOCIAL MEDIA - Erpida Ompusungu; Nopita Sitompul (ISER (Indonesian Science Education Research), 2020)
Drug trafficking is one of the problems that still occurs in Indonesia and is now a serious problem, especially for adolescents or the younger generation. Adolescents are of productive age who really need special attention, where the level of self-search tends to be unstable and the mindset is instant. Therefore there is anxiety among the community including parents about the behavior of adolescents who are still unable to control themselves in things that are dangerous and destructive to themselves and tend to lead to acts of violating norms or legal rules. So there is a need for efforts to prevent abuse. drugs. One of the triggers for the increasing level of drug abuse is the lack of socialization to the public which results in minimal information about the dangers of narcotics abuse. The purpose of this study was to determine the function of posters on social media in making it easier for the public to obtain information regarding the dangers of narcotics abuse. The instrument used was a poster design uploaded on social media. The method used in data collection is primary data which is obtained directly through comments and suggestions from followers. The results obtained are the easier it is for the public to obtain information about the dangers of drugs as a solution in preventing drug abuse. It is hoped that the use of posters on Instagram social media can become a media of information about the dangers of drug abuse